Psychological Dynamics of Travel Business Students’ Adaptation to Internships: An Interpretive Study in Indonesia - Ghifari Yuristiadhi Masyhari Makhasi; Anita Aisah (E-Journal of Tourism, 2026)
Industrial internships are a key component of vocational higher education, particularly in the tourism sector, as they bridge academic learning and workplace practice. However, students often encounter challenges when adapting to professional environments. This study aims to examine the psychological dynamics shaping students’ adaptation to industrial internships. This research adopts a small-scale qualitative interpretive approach based on in-depth structured interviews with 10 travel business students undertaking internships at travel agencies in Yogyakarta and Bali, Indonesia. The data were analyzed using thematic analysis to identify recurring patterns in students’ experiences. The findings reveal two major thematic groups influencing adaptation: facilitators and barriers. Facilitating factors include supportive work environments, positive interpersonal relationships, and clear internship structures, which enhance students’ confidence and sense of belonging. In contrast, barriers such as unclear job instructions, strict organizational cultures, logistical constraints, and language challenges generate stress and hinder adjustment. The adaptation process generally unfolds over one to two months, with an initial phase of role clarification followed by deeper social and cultural integration into the workplace. These findings highlight the importance of organizational and psychological support in internship design. While limited in scale, this study provides insights into how tourism students navigate early professional experiences and underscores the need for structured and supportive internship environments in the tourism industry.